Understanding community media - Howley, Kevin; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2010)
This collection introduces students to the expanding field of media studies in an accessible and engaging fashion. With original contributions from a team of well-known experts, media activists, and promising young scholars, this volume examines community media from theoretical, empirical, historical, and practitioner perspectives.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Local mass media; Electronic books